Malaysian vernacular school teachers' opinion in using language of thinking in teaching Science to young learners in primary 1 - Hoo, Li Shiong; Ali, Nornabilah; Ramanathan, Vaitheswary; Subarhinam, Thurka Devi; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Teaching the language of thinking is a subject that had gained much popularity as it concerns our future generation. This research reports preliminary reports on the investigation on school teachers’ opinions in using the language of thinking to help young learners (Primary 1) in understanding teaching materials better. In this research, the concentration is on one specific group of teachers – Primary 1 Science teachers in Malaysia. Individual interviews of five Primary 1 Science school teachers from five different schools we conducted. The interviews tarted out in gathering information about awareness of the concept of ‘language of thinking.’ It was followed by simple explanation of the language of thinking. Interviewees were then asked if they think incorporating the language of thinking in their teaching could help their students in understanding the materials better. The results of the interview showed a zero score in the awareness of the concept ‘language of thinking.’ They all unanimously agreed that incorporating the language of teaching would help their learners in achieving better understanding of their teaching.